Aktivitas Antibakteri Hand Sanitizer Komersial Pada Staphylococcus aureus - Nur Khikmah; Niken Apriliani (Pelantar Press, 2026)
Hand hygiene is an effective way to prevent the transmission of infectious diseases caused by Staphylococcus aureus. The use of hand sanitizer is a practical alternative in maintaining hand hygiene, especially when water and soap are unavailable. Commercial hand sanitizers are widely available on the market with different compositions and concentrations of active ingredients, allowing for variations in their ability to inhibit bacterial growth. The aim of this research was to determinate the antibacterial activity of commercial hand sanitizer against S. aureus. The antibacterial activity was determinated using well diffusion method. The results showed that 2 brands of hand sanitizers produced a radical zone, 1 brand produced an irradical zone, and 2 brands did not produce an inhibition zone on S. aureus. The conclusions of the research was that commercial hand sanitizer containing active ingredients combined with ethanol (an alcohol derivative) and triclosan were more able to inhibit S. aureus compared that hand sanitizer containing only alcohol or alcohol derivatives. The inhibition against S. aureus was categorized as very strong.